Are we 'survival machines'? A Brief Reflection on the Ends and Norms of Nature - Piasentier, Marco (Scenari, 2021)
Clocks are for measuring time; typewriters are for writing: when we examine artifacts, we tend to attribute teleological and normative functions to them. When we consider biological entities, can we attribute natural purposes and norms to them? Are eyes for seeing and hearts for pumping blood? This article challenges those philosophical approaches that attempt to ground teleological and normative functional attributions in the process of natural selection. If Darwinian theory outlines a worldview devoid of natural purposes and norms, then there is reason to be suspicious also about the pervasive use of design metaphors, since they indirectly legitimate the terms of debate favored by teleological and normative views of nature: why keep resorting to metaphors that represent organisms and, therefore, the human animal, as “survival machines” (Dawkins), if there is no teleology and normativity in nature?